Islamic microfinance: the role of charity and social capital in alleviating poverty and asset building - Hamdan, Hamdino; Abdullah, Moha Asri; Mohamad, Noorihsan (2015)
Most of the poor has high expectation for various forms of microfinancial sources from both the formal as well as the informal sectors. These sources of finance are highly needed by the poor to start and operate their productive activities such as microenterprises that generate sufficient income, hence relieve them from poverty. In addition, Islamic microfinance programme (IMP) which is based on Syariah and Islamic Finance concept has a very high potential in helping the poor to expand and diversify their economic activities, and increase their contribution towards the development of entrepreneurial activities. A significant proportion and allocation of resources has been allocated for IMP to help enterprise creation and development, but the outcome has not been made available. Malaysia is not exceptional to this as there are numerous financial assistance provided and different Islamic micro finance schemes have been introduced, unfortunately, to what extent its effectiveness and its coverage are difficult to ascertain. Hence this study was conducted to evaluate the effectiveness of lMP on financial wellbeing, asset building and poverty alleviation of the participants through enterprise creation and expansion. Results of the study show that IMP (based on charity and social capital concept) is capable to increase the participants’ income and asset generation. Eventually taking them out of the poverty line.